Myanmar/Burma inside challenges, outside interests - Rieffel, Alexis 1941-. (Washington, D.C. Brookings Institution Press, 2010)
Through the eyes of ASEAN members, neighbors China and India, and the United States, examines current state of affairs in Myanmar/Burma and focuses on national reconciliation and economic development, as the country approaches multiparty elections in fall 2010 and after the Obama presidency has initiated a new approach to relations"--Provided by publisher.
Keywords: Burma -- Politics and government -- 1988-.; Burma -- Foreign relations -- 1948-.